2019
DOI: 10.1039/c9ra07158j
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two sequential extraction procedures for tungsten fractionation in the tungsten mining soils

Abstract: The Wenzel SEP showed higher extraction efficiency in potentially mobile tungsten fractions, especially for the tungsten associated with iron hydroxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…For heavy metals present in a cationic form, there are various sequential extraction procedures (SEP) that can be used; for tungsten, it is necessary to select extractions for a metal present in the anionic form. A comparison with the Tessier SEP [51], which is often used for cationic metals, showed that the sequential extraction scheme used by Wenzel [52] for the study of arsenic was also the most appropriate SEP for estimating tungsten mobility and bioavailability [53]. Soil chemistry assesses the distribution of metal in the various pools.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For heavy metals present in a cationic form, there are various sequential extraction procedures (SEP) that can be used; for tungsten, it is necessary to select extractions for a metal present in the anionic form. A comparison with the Tessier SEP [51], which is often used for cationic metals, showed that the sequential extraction scheme used by Wenzel [52] for the study of arsenic was also the most appropriate SEP for estimating tungsten mobility and bioavailability [53]. Soil chemistry assesses the distribution of metal in the various pools.…”
mentioning
confidence: 99%
“…Whichever SEP is used, most of the tungsten is generally recovered in the last residual phase, which shows the chemical form of tungsten that is most strongly retained by soil solid components. These residual fractions pose the lowest environmental risk [53,54].…”
mentioning
confidence: 99%
“…The role of such minerals as scheelite and W-containing goethite in the W distribution in the soil appears insignificant. Sequential extraction procedures for fractionation of W (Li et al, 2019) are required to determine the proportion of different forms of W in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of soil properties (pH, organic matter, cation exchange capacity, clay, silt, and sand) and W environmental availability were performed on the 2 mm air-dried soil fraction by standard methods [37]. To evaluate W environmental availability (BAV) the Wenzel sequential extraction procedure (SEP) [38] was used as it is considered the most appropriate for tungsten speciation [39].…”
Section: Tungsten Environmental Availability and Bioaccessibility Eva...mentioning
confidence: 99%
“…The five fractions of the Wenzel SEP were determined using the following extractions: F1: 0.05 M (NH 4 ) 2 SO 4 , 4 h, 25 • C ratio soil/extractant 1:25; F2: 0.05 M NH 4 H 2 PO 4 , 16 h, 25 • C ratio soil/extractant 1:25; F3: 0.2 M NH 4 -oxalate buffer in the dark (pH = 3.25), 4 h, 25 • C ratio soil/extractant 1:25; F4: 0.2 M NH 4 -oxalate buffer + 0.1 M ascorbic (pH = 3.25), 0.5 h, 96 • C ratio soil/extractant 1:25; and F5: HNO 3 -HClO 4 , 180 • C ratio soil/extractant 1:50 [39]. Tungsten recovery by this method ranged from 98.8% to 101%.…”
Section: Tungsten Environmental Availability and Bioaccessibility Eva...mentioning
confidence: 99%